Research on Multiple Signal Synthesis Methods in Space Electromagnetic Environment Simulation. Issue 1 (May 2021) - Yuan, Wang; Wei, Tan; Lidong, Cui; Ying, Li
Abstract: This paper proposes three spatial electromagnetic signal environment concepts from three levels: general electromagnetic signal environment, relative electromagnetic signal environment and electronic warfare signal environment. It can solve the difficult problem of comprehensive, accurate and targeted description of the electromagnetic environment in the space electromagnetic environment simulation of the spacecraft. This paper studies the synthesis method of various types of signals contained in the three electromagnetic signal environments in a certain area, and provides a reference for the accurate simulation of the dynamic and intuitive, hierarchical electromagnetic environment situation in a certain area of space.